2020
DOI: 10.3389/fcimb.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Intracellular Calcium Homeostasis as a Therapeutic Target Against Trypanosoma cruzi

Abstract: There is no effective cure for Chagas disease, which is caused by infection with the arthropod-borne parasite, Trypanosoma cruzi. In the search for new drugs to treat Chagas disease, potential therapeutic targets have been identified by exploiting the differences between the mechanisms involved in intracellular Ca 2+ homeostasis, both in humans and in trypanosomatids. In the trypanosomatid, intracellular Ca 2+ regulation requires the concerted action of three intracellular organelles, the endoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 116 publications
3
38
0
1
Order By: Relevance
“…Others showed that active TGF-β is very important during T. cruzi infection [ 21 ]. T. cruzi has been reported to dysregulate calcium homeostasis to facilitate cellular infection [ 22 ]. Calcium binds to calmodulin (CaM) and activates the phosphatase calcineurin and CaM Kinase II [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others showed that active TGF-β is very important during T. cruzi infection [ 21 ]. T. cruzi has been reported to dysregulate calcium homeostasis to facilitate cellular infection [ 22 ]. Calcium binds to calmodulin (CaM) and activates the phosphatase calcineurin and CaM Kinase II [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combine of both actions will lead to a large parasite-specific intracellular accumulation of Ca +2 [69]. Since disruption of the intracellular Ca +2 homeostasis has been described as an important drug target in trypanosomatids [40,42,71], miltefosine could indeed be an interesting drug candidate to pursue for Chagas disease. In fact, several studies have reported in vitro susceptibility of T. cruzi parasites to miltefosine [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, trypanocidal compounds such as squalene synthase inhibitors may also cause contractile vacuole enlargement (Braga et al, 2004 ). It remains to be determined whether the osmoregulatory mechanism could be involved in cell death mechanism triggered by fungal derivatives, but calcium homeostasis is involved in the mode of action of antiparasitic agents on Leishmania donovani (Pinto-Martinez et al, 2018 ) and Trypanosoma cruzi (Benaim et al, 2020 ). Lipid body formation may comprise an escape mechanism as this compartment is an intracellular site of synthesis of prostaglandins, such as PGF 2a , inhibiting different facets of the immune response (Vallochi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%